A novel chitosan microsphere as food processing enzyme immobilization carrier and its application in nucleotide production - Xiao-Yan Yin; Rui-Fan Yang; Zhong-Hua Yang (Food Chemistry: X)
Developing a robust and safe carrier for enzyme immobilization is crucial for their application in the food processing industry. In this study, a novel crosslinked chitosan microspheres (CSMs) were prepared using glutaraldehyde (GA) as the crosslinking agent, using a newly developed emulsification-neutralization combined method. Nuclease P1 (NP1) was immobilized onto these microspheres, the maximum activity of NP1@CSMs-GA reach to 53,859.4 U/g. The activity recovery yield reach to 75 %. Compared to the free NP1, the stability of NP1@CSMs-GA was significantly enhanced. Its vmax and Km is 895.71 mg/(g·min) and 77.27 mg/mL respectively. This NP1@CSMs-GA was utilized in production of nucleotides through hydrolysis of RNA. In BSTR, NP1@CSMs-GA retained more than 75.1 % initial activity after 10 cycles of reuse. Moreover, in PBR, the RNA hydrolysis conversion rate maintained 81 % after 24 h of continuous operation. These results demonstrate that NP1@CSMs-GA exhibits excellent reusability and production stability in practical processes.